Intraoperative Nerve Monitoring in Thyroidectomies for Malignancy: Does It Matter?. Issue 6 (June 2022) - Leonard-Murali, Shravan; Ivanics, Tommy; Nasser, Hassan; Tang, Amy; Singer, Michael C.
Background: Recurrent laryngeal nerve (RLN) injury and postoperative hypocalcemia are potential complications of thyroidectomy, particularly in malignancy. Intraoperative nerve monitoring (IONM) remains controversial. We sought to evaluate the impact of IONM on these complications using a national data set. Methods: The American College of Surgeons National Surgical Quality Improvement Program thyroidectomy-targeted data set was queried for patients who underwent thyroidectomies from 2016 to 2017. Patients were grouped according to IONM use. Logistic regression models were constructed to evaluate associations of variables with 30-day hypocalcemic events (HCEs) and RLN injury. Associations were expressed as odds ratios (ORs) with 95% confidence intervals (95% CIs). A subgroup analysis was performed of patients with malignancy. Results: A total of 9527 patients were identified; 5969 (62.7%) underwent thyroidectomy with IONM and 3558 (37.3%) without. By multivariable analysis, IONM had protective associations with HCE (OR = .81, 95% CI = .68-.96; P = .013) and RLN injury (OR = .83, 95% CI = .69-.98; P = .033). Malignancy increased risk of HCE (OR = 1.21, 95% CI=1.01-1.45; P = .038) and RLN injury (OR = 1.22, 95% CI = 1.02-1.46; P = .034). A large proportion (5943/9527, 62.4%) of patients had malignancy; 3646 (61.3%) underwent thyroidectomy with IONM and 2297 (38.7%) without. In the subgroup analysis, IONM had stronger protective associations with HCE (OR = .73, 95% CI = .60-.90; P = .003) and RLN injury (OR = .76, 95% CI = .62-.94; P = .012). Discussion: Malignancy was associated with increased risk of HCE and RLN injury. Intraoperative nerve monitoring had a protective association with HCE and RLN injury, both overall, and in the malignant subgroup. Intraoperative nerve monitoring was correlated with improved thyroidectomy outcomes, especially if the indication was malignancy. This warrants further study to clarify cause and effect.